Sustainability, Social Impact, Learning and Training Innovation in Online Experimentation - Bochicchio, Mario A.; Vaira, Lucia (International Journal of Interactive Mobile Technologies (iJIM), 2017)
Experimentation is an essential ingredient in any learning strategy about Sciences and Technologies (SciTech in the following). That is why the research on online experimentation is paramount to help confront the skill shortage in SciTech disciplines, by stimulating the development of more effective online learning and training approaches. Nonetheless, in this sector "functional" aspects are often overrated by researchers and no specific attention is paid to the sustainability of their proposals or to the possibility to analyze and improve the achieved social impact. A better integration among these aspects is then essential to move online experimentation research out of its infancy, to improve its perceived value and to increase its diffusion.